Isolation and Screening of Cellulolytic Soil Bacteria from Dramaga Forest in Bogor - Weridyaningrum, Ratu; Imaningsih, Witiyasti; Fasha, Gusti Nur Aida (Universitas Atma Jaya Yogyakarta, 2025)
Cellulolytic bacteria can produce cellulase enzymes, which allow them to degrade cellulose into simpler chemicals while using it as a growth substrate. These bacteria have drawn a lot of interest due to their unique properties and potential uses, such as in agriculture and the food industry. Soil is one of the habitats of cellulolytic bacteria. This study aims to determine the potential and screening of cellulolytic bacterial isolates. Cellulolytic bacteria were isolated from soil samples and cultured using selective Carboxyl Methyl Cellulose (CMC) media. Five purified isolates were collected, and their cellulase enzyme activity was qualitatively assessed using the Congo red test. Isolated bacteria code Area Jalan Setapak (AJS1) produced a higher clear zone index and will be used for further testing. Quantitative analysis of isolate AJS1 revealed its highest enzyme activity after ten minutes of incubation, with 0.0049 U/mL unit activity and 0.018 U/mg specific activity. Based on morphological and biochemical characteristics, isolated AJS1 was identified as Corynebacterium spp.